Excitation of the three principal spin waves in yttrium iron garnet using a wavelength-specific multi-element antenna - Wonbae Bang; Matthias B. Jungfleisch; Jinho Lim; Jonathan Trossman; C. C. Tsai; Axel Hoffmann; John B. Ketterson (AIP Advances, 2018)
We report systematic measurements of the dispersion of long wavelength spin waves for the magnetic field along the three principal directions (supporting the forward volume, backward volume and Damon-Eshbach modes) of a 3.05 μm thick yttrium iron garnet film on a lattice-matched (111) gadolinium gallium garnet substrate obtained using a lithographically patterned, multi-element, 50 μm spatially-resonant, antenna.